SOUTH-AMERICAN REGIONALISM AND THE TURN TOWARDS DISINTEGRATION: SOME REFLECTIONS - Neves, Barbara Carvalho [UNESP]; Pasquariello Mariano, Karina Lilia [UNESP] (Colegio Mexico, A C, Dept Publicaciones, 2022)
The beginning of the second decade of the 21st century brought with it setbacks to the drive for Latin American regional unity, marked by the dismantling of Unasur, the paralysis of ALBA and problems with Celac and Mercosur. Many studies on the topic point to greater tensions in these regional mechanisms as a result of various circumstantial factors such as the death of the Venezuelan President Hugo Chavez, the increasing polarization of politics in Brazil and Argentina (especially since the impeachment of Dilma Rousseff), the Right Turn taken by the region, and the expanding presence of extraregional actors such as China and the United States. With a process-based and institutional analysis, this article discusses how South American regional institutions reacted to the current periods of crisis. It argues that the dismantling of Unasur is not simply a result of the systemic changes undergone in this period, but a reflection of the Latin American institutional direction of travel and its critical antecedents. It concludes that the historical context might be the opportunity that gave rise to this process of disintegration, but not its cause.
Keywords: economic integration; intergovernmental organization; South America; regionalism